Особенности развития лидерского потенциала у будущих инженеров - Мовчан, Яна Александровна (НТУ "ХПИ", 2017)
Статья описывает программу развития лидерского потенциала будущих инженеров. Предложенная программа содержит несколько блоков: мотивационный – для повышения мотивации к профессиональной деятельности; социально-адаптивный – для развития коммуникативных качеств и готовности к межличностному взаимодействию; стратегически-профессиональный – для работы с представлениями будущего инженера о своей профессиональной роли и проработки профессионально необходимых качеств. Для реализации программы использованы такие формы работы как мини-лекции, семинары-беседы, психологические упражнения, техники и деловые игры. Представлены результаты, демонстрирующие эффективность разработанной программы. Эмоциональные, мотивационные, волевые и коммуникативные показатели имеют позитивную динамику после внедрения тренинговой программы.

The article describes a program for developing the leadership potential of future engineers. The proposed program contains several blocks: motivational – for developing motivation to professional activity, socially adaptive – for developing communicative characteristics and preparing for interpersonal interaction, strategic professional – for training future engineer’s imaginations according to their professional role and their professional important features training. Program consists of such type of work as mini-lectures, communicative seminars, psychological exercises, techniques, business games. Presented results are demonstrating the effectiveness of the developed program. Emotional (stability, restraint), motivational (to professional activity, self-development, achievements, complex purposes), volitional (self-control) and communicative (sociability, boldness in communications, dominance, stable relations) attributes have shown positive dynamics after introduction training program.
Features of leadership potential development of future engineers
Keywords: качества лидерские; подготовка профессиональная; подготовка специалистов; образование высшее; личность; leadership qualities; professional training